Rivet user manual - Buckley, Andy; Butterworth, Jonathan; Grellscheid, David; Hoeth, Hendrik; Lönnblad, Leif; Monk, James; Schulz, Holger; Siegert, Frank (Computer physics communications, 2013)
This is the manual and user guide for the Rivet system for the validation and tuning of Monte Carlo event generators. As well as the core Rivet library, this manual describes the usage of the rivet program and the AGILe generator interface library. The depth and level of description is chosen for users of the system, starting with the basics of using validation code written by others, and then covering sufficient details to write new Rivet analyses and calculational components. Program title: Rivet Catalogue identifier: AEPS_v1_0 Program summary URL:http://cpc.cs.qub.ac.uk/summaries/AEPS_v1_0.html Program obtainable from: CPC Program Library, Queen’s University, Belfast, N. Ireland Licensing provisions: Standard CPC licence, http://cpc.cs.qub.ac.uk/licence/licence.html No. of lines in distributed program, including test data, etc.: 571126 No. of bytes in distributed program, including test data, etc.: 4717522 Distribution format: tar.gz Programming language: C++, Python. Computer: PC running Linux, Mac. Operating system: Linux, Mac OS. RAM: 20 MB Classification: 11.9, 11.2. External routines: HepMC (https://savannah.cern.ch/projects/hepmc/), GSL (http://www.gnu.org/software/gsl/manual/gsl-ref.html), FastJet (http://fastjet.fr/), Python (http://www.python.org/), Swig (http://www.swig.org/), Boost (http://www.boostsoftware.com/), YAML (http://www.yaml.org/spec/1.2/spec.html) Nature of problem: Experimental measurements from high-energy particle colliders should be defined and stored in a general framework such that it is simple to compare theory predictions to them. Rivet is such a framework, and contains at the same time a large collection of existing measurements. Solution method: Rivet is based on HepMC events, a standardised output format provided by many theory simulation tools. Events are processed by Rivet to generate histograms for the requested list of analyses, incorporating all experimental phase space cuts and histogram definitions. Restrictions: Cannot calculate statistical errors for correlated events as they appear in NLO calculations. Unusual features: It is possible for the user to implement and use their own custom analysis as a module without having to modify the main Rivet code/installation. Running time: Depends on the number and complexity of analyses being applied, but typically a few hundred events per second.